The following steps can be applied to find the inverse of a function. We will go through the steps by the example f(x) = 2x + 3 to find its inverse.

Thus there are four steps in finding the inverse of a function

**Replace f(x) with y**y = 2x + 3

**Write 'x' in place of 'y' and 'y' in place of 'x'**x = 2y + 3

**Solve for 'y'**2y = x - 3

y = (x - 3)/2

**Replace y with f^-1(x)**f^-1(x) = (x - 3)/2

**f^-1(x) is the inverse of f(x)**Thus there are four steps in finding the inverse of a function

- Replace f(x) with y
- Write x in place of y and y in place of x
- Solve for y
- Replace y with f(x)